Usability of the "Systematic Review Support" computer system: a methodological study - Fernanda Martins Dias Escaldelai; Leandro Escaldelai; Denise Pimentel Bergamaschi (Universidade de São Paulo, 2024)
Objective: to evaluate the usability of the "Systematic Review Support" computer system. Method: methodological study involving 21 students who evaluated the computer system in a remote and synchronous usability test. Two activities were carried out, containing 21 tasks simulating the initial steps of a review study, proposals for eliminating duplicate references, selecting studies and resolving disagreements between evaluators. At the end, participants answered the System Usability Scale questionnaire. The measures used were: completion rate with assistance (effectiveness) and time to complete the task (efficiency). The data was described in a table using the mean, standard deviation, minimum and maximum values. Results: in a total of 21 tasks, the participants had an assisted completion rate of 9% and an average time of 55.1 minutes (the expected time being 60 minutes). The average score provided by the System Usability Scale instrument was 82.4 (considering a score from 0 to 100), median 85; minimum value 35 and maximum 97.5. Conclusion: the computer system has the effectiveness and efficiency parameters required of a computer review tool. It has a usability score of 82.4 on a scale of 0 to 100 assessed by the System Usability Scale instrument. The version presented incorporates the adjustments identified in the test in use.